Physico-chemical properties of acid soils from Madhupur Tract and Northern & Eastern Piedmont Plains of Bangladesh (Asian Journal of Medical and Biological Research, 2021)
Soil reaction is an important issue that adversely affects soil fertility and crop productivity. Twenty five representative soil samples from farmers’ fields of Ramchandrakura, Bishgiripar, Andharupara and Nayabil villages of Nalitabari upazila under Sherpur district (AEZ 22-Northern and Eastern Piedmont Plains) and twenty soil samples from farmers’ fields of Bakta, Nishchintopur, Boril and Kaladaho villages of Fulbaria upazila under Mymensingh district (AEZ 28-Madhupur Tract) were collected and analyzed to study the physico-chemical properties of acid soils. Among 45 samples, 13 were sandy loam, 17 were silt loam, 10 were loam, 2 were clay loam and 3 were loamy sand in texture. Soil pH was very strongly acidic to strongly acidic. The soil pH of AEZ 22 varied from 3.81 to 4.78 and that of AEZ 28 varied from 3.96 to 5.11. The organic C of Nalitabari soil varied from 0.50 to 1.35% and that of Fulbaria soils ranged from 0.50 to 1.27% showing low to medium status. The status of nutrient elements viz. N, P, K and S in most of the samples was very low or very low to medium. Total N contents of AEZ 22 varied from 0.06 to 0.14% and that of AEZ 28 varied from 0.07 to 0.16%. Available P in soils of AEZ 22 varied from 3.25 to 26.45 ppm and that in soils of AEZ 28 ranged from 2.45 to 16.62 ppm. Exchangeable K in AEZ 22 soils varied from 15.13 to 92.41 ppm and that in AEZ 28 soils varied from 16.09 to 98.41 ppm. Available S in AEZ 22 soils varied from 1.68 to 33.70 ppm and that in AEZ 28 soils from 3.95 to 27.52 ppm. Therefore, these acid soils should be amended with liming materials and fertilized with inorganic fertilizers and organic manures for successful crop production.Asian J. Med. Biol. Res. March 2021, 7(1): 12-20